Micropropagation of juvenile and adult Quercus suber L. - Manzanera, J A; Pardos, J A (Plant Cell, Tissue and Organ Culture, 1990)
This paper describes research on the application of tissue culture techniques to the micropropagation of cork oak (Quercus suber L.), a forest species of ecological and industrial importance in the Mediterranean area. Apical buds and nodal stem segments were employed as initial explants. Their origins were young seedlings, stump sprouts and sprouts formed on cuttings collected from old trees. The action of the mineral medium and growth regulators was studied in the multiplication stage. Media with low concentrations of ions, such as Sommer's or Heller's, are more suitable for growth and proliferation of explants than other media richer in salts. It was also observed that cytokinin (BA) must be present for the culture development. Adding low concentrations of auxin (NAA) to the medium improves the multi- plication rate, especially in vegetative material of adult origin. The auxin type is the most important factor in the promotion of rhizogenesis. The method of application determines the quality of the root system. Treatment with low concentrations of IBA added to the rooting medium gives the best results. High sucrose concentration also improves rooting. Diluting the mineral rooting medium is slightly favourable, although there is no significant difference between it and the standard mineral concentration.
Keywords: Cork oak; micropropagation; Quercus suber; rooting; tissue culture